Antimicrobial stewardship in Australian hospitals: how does compliance with antimicrobial stewardship standards compare across key hospital classifications?. Issue 4 (4th December 2020) - Jones, Renee; Carville, Kylie; James, Rodney
Abstract: Background: There is little information on the prevalence and type of antimicrobial stewardship (AMS) activities that are currently occurring in Australian hospitals. Objectives: To determine what AMS activities are currently occurring in Australian hospitals, identify gaps in compliance with the Australian Commission on Safety and Quality in Health Care (ACSQHC) standards and determine perceived barriers and enablers for implementing AMS programmes. Methods: A cross-sectional survey open to all Australian hospitals, conducted online and available to hospitals between November 2016 and July 2017. Results: Responses were received from 254 hospitals. Compliance with ACSQHC AMS essential activities was high, except for essential activity 3 (post-prescription reviews), which was conducted by only 39% of respondent hospitals. Importantly, compliance varied by hospital remoteness classification for all activities except essential activity 1 (availability and endorsement of guidelines) and additional activity 4 (publishing antimicrobial susceptibility data annually), with major city hospitals having the highest compliance across all activities. The three most frequently reported barriers to implementing AMS programmes were a lack of training and education, lack of pharmacy resources and a lack of willingness from medical officers to change. Conclusions: Due to low response rates from certain hospital groups, the survey results are not generalizable to all Australia hospitals. This survey has identified that several gaps in compliance still exist and outlines the need to address lower AMS compliance in hospitals located outside major cities. The key barriers and enablers for AMS programme implementation identified should be used to inform future strategies.